Nurses' structured health teaching, mothers' socio-demographic characteristics and their knowledge and skills on diarrhea - Malapitan, Rosemarie L. Damasco
This study investigated the effects of structured health teaching (SHT) activity of nurses on the knowledge and skills of mothers concerning the prevention and treatment of diarrhea. Specifically, it aimed to determine if there was a difference in the level of knowledge and skills of mothers before and after the structured health teaching. It also determined whether there was a significant relationship between selected socio-demographic variables and the knowledge and skills of the mothers.The health teaching activity on Prevention and Treatment of Diarrhea (PDT) conducted by nurses consisted of a lecture, demonstration and return demonstration. The health teaching was directed to all mothers who sought consultation at the Out Patient Department (OPD) of the provincial hospital in Region IV with children under five years old, afflicted with acute gastroenteritis with no signs of dehydration. The study included eighty (80) mother as participants.The structured health teaching of PTD was approximately 12 minutes of lecture-demonstration on the following: identification of signs and symptoms of diarrhea and measures to prevent it (handwashing, safe disposal of babies' feces, proper use of latrine, boiling of drinking water and sterilization of feeding bottles). It also included home fluid therapy, ways to prevent malnutrition, Oresol preparation and administration and identification of danger signs of diarrhea. The lecture was also supported by visual aids (pictures and flipchart) on Oresol preparation and danger signs of diarrhea. This structured health teaching activity was uniquely different from other health teachings being utilized at the hospital's OPD in the sense that the four nurses who conducted the SHT were trained by the investigator on the content and method of the protocol on the health teaching plan for diarrhea which was translated in the vernacular. It was an individualized teaching encouraging the participants to ask questions or clarifications.A pre-experimental one group pre-test and post-test design was used. Baseline data were determined by answering interview schedule on the level of knowledge. An observation checklist was utilized to determine whether the required skills in performing handwashing and Oresol preparation were done or not. The participants were required to come back after three to five days for post evaluation test and to return demonstrate on proper handwashing and Oresol preparation. This was a strategy to check whether learning took place.The profile of the study population was determined using descriptive statistics. Mean scores of the participants on written tests were computed to determine their level of knowledge and skills. T-test was done to determine significant differences in the participants' knowledge and skills before and after the structured health teaching.Significant relationship of selected demographic variables with knowledge, and skills was measured using Pearson p, with the level of significance set at .05.